1993
DOI: 10.1161/01.atv.13.8.1164
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate formation is more strongly inhibited at high shear rates by dRGDW, a synthetic RGD-containing peptide.

Abstract: The effect of D-Arg-Gly-Asp-Trp (dRGDW), a synthetic RGD-containing peptide, on platelet adhesion and aggregate formation on various purified adhesive proteins and the extracellular matrix of endothelial cells was investigated with anticoagulated blood recirculating through a parallel-plate perfusion chamber. Aggregate formation on the extracellular matrix of phorbol myristate acetate (PMA)-stimulated endothelial cells and on collagen type I was more strongly inhibited by dRGDW at higher shear rates than at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Interestingly, to date no study has showed the equal importance of these receptors in the signaling. Some studies showed that GPVI is the main receptor mediating both adhesion and the signaling response (Nieswandt et al, 2001;Masberg et al, 2003), while others reported the importance of ␣ 2 ␤ 1 in adhesion and aggregation of platelets (Saelman et al, 1994). Therefore our results may bring a new perspective to the recruitment of the platelet receptors in the signaling pathway under no-flow conditions.…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, to date no study has showed the equal importance of these receptors in the signaling. Some studies showed that GPVI is the main receptor mediating both adhesion and the signaling response (Nieswandt et al, 2001;Masberg et al, 2003), while others reported the importance of ␣ 2 ␤ 1 in adhesion and aggregation of platelets (Saelman et al, 1994). Therefore our results may bring a new perspective to the recruitment of the platelet receptors in the signaling pathway under no-flow conditions.…”
Section: Discussionsupporting
confidence: 52%
“…Consistent with these findings, it was previously shown that inhibition of GPVI via the monoclonal antibody 9O12 reduced the platelet aggregate formation under flow conditions but still permits the initial platelet adhesion via integrin α 2 ß 1 with the adherence of numerous single platelets [15]. The inhibition of platelet activation via anti‐α IIb ß 3 antibodies or RGD‐containing peptides also resulted in increased platelet adhesion to collagen, as platelets that are not incorporated in the aggregates are now available to adhere [16]. Remarkably, the PFA100 closure time for collagen/ADP was shortened for the patient; 62 and 64 s with a reference value of CT/ADP = 71–118 s. The closure time for collagen/epinephrine was normal; 113 s with a reference value of CT/EPI = 94–193 s. Her mother had normal PFA100 closure times.…”
Section: Resultsmentioning
confidence: 99%
“…Monomeric collagen type III was solubilized in 50 mmol/L acetic acid and sprayed with a density of 30 g/cm 2 on glass coverslips with a retouching airbrush (Badger model 100, Badger Brush Co). 12,13 After the spraying procedure, the collagen surface was blocked for 1 hour with 1% human albumin in PBS (10 mmol/L phosphate buffer, pH 7.4, and 0.15 mol/L NaCl) to prevent nonspecific protein binding during the subsequent perfusion and then incubated with 20 g/mL vWF in PBS for 2 hours.…”
Section: Coating Of the Coverslipsmentioning
confidence: 99%